Land Suitability Analysis for Potential Agriculture Land Use in Sambhunath Municipality, Saptari, Nepal - Karna, Bikash Kumar; Shrestha, Shobha; Koirala, Hriday Lal (The Geographic Base, 2021)
Rapid and unplanned urbanization and haphazard infrastructure development causes pressure on the finite land resource and there is urgent need to preserve the arable land for food security. Land suitability analysis is a technique in which the land quality assessment is performed through interpretation of land properties for allocation of lands for particular use. The present paper attempts to conduct a land suitability analysis to determine the potential sites for agriculture land use in Sambhunath municipality of Saptari district. The criteria/ factors for the land suitability analysis were identified through literatures and modified in the local context through expert opinions and focus group discussions. The evaluation of agriculture land is accomplished using Analytic Hierarchy Process (AHP), Multi-Criteria Evaluation (MCE) and Geographic Information System (GIS). Agriculture suitability index was developed and optimized qualitatively through the strength, weakness, opportunity, and threat (SWOT) analysis. Finally, potential agriculture suitability index map is prepared. The analysis shows almost 3139 ha (29%) lands as 14 highly suitable and 3001 ha (28%) of moderately suitable agriculture land within the municipality. Almost all the suitable agriculture land is located at low land with flat terrain to gentle slope having high natural fertility and mainly in land capability classes I and II. The unsuitable and poorly suitable agriculture land is occupied in the undulating areas and hilly terrain of the Siwalik hill. The study found the GIS tool integrated with MCE-AHP useful in land suitability evaluation process and anticipated that it could act as the planning tool to allocate lands in land use planning for sustainable agricultural practices.